Delayed onset of posterior reversible encephalopathy syndrome in a case of scleroderma renal crisis with maintenance hemodialysis: Case report and literature review. Issue 52 (December 2016) - Chen, Ching-Yang; Hung, Shin-Yuan; Lee, Yi-Jer; Lin, Yi-Chan; Pai, Chu-Cheng
Abstract: Introduction: In some cases, scleroderma renal crisis (SRC) is not easily distinguishable from other thrombotic microangiopathies such as thrombotic thrombocytopenic purpura, especially when the presentation includes neurological or extra-renal manifestations. Here, we present a case of SRC who developed a rare neurotoxic complication, posterior reversible encephalopathy syndrome (PRES). A 36-year-old man with a history of diffuse cutaneous systemic sclerosis developed SRC and acute-on-chronic renal failure and ultimately required maintenance hemodialysis. Three weeks after starting hemodialysis, the patient presented with confusion and a new-onset seizure disorder. Laboratory examinations revealed thrombocytopenia, a low haptoglobin level, and schizocytes on a blood smear. SRC-related PRES was considered first after PRES was confirmed by brain magnetic resonance imaging. Antihypertensive therapy comprising captopril and amlodipine was administered, and the patient experienced a complete neurological recovery 3 days later without plasma exchange. In all previously reported cases of SRC-associated PRES, PRES developed before hemodialysis. Our report is, therefore, the first to describe a case of onset of SRC-related PRES 3 weeks after the initiation of maintenance hemodialysis. Conclusion: This case demonstrates that microangiopathy and extra-renal manifestations can develop even in SRC patients with end-stage renal disease and that these manifestations can be successfully managed with angiotensin-converting enzyme inhibitors (ACEIs) and aggressive blood pressure control. We recommend continuing ACEI therapy if elevated blood pressure persists after maintenance hemodialysis.